Modernisasi Sistem Administrasi Perpajakan dan Pelayanan Fiskus Dalam Meningkatkan Kepatuhan Wajib Pajak Orang Pribadi - Eva Fauziah Ahmad; Tito Marta Sugema Dasuki (Journal of Innovation in Management, Accounting and Business, 2023)
Tax is a source of income for a country. However, the revenue obtained from taxes is largely determined by taxpayer compliance. There are several factors that can affect taxpayer compliance, two of which are the modernization of the tax administration system and tax administration services. This study aims to determine the compliance of individual taxpayers affected by the modernization of the tax administration system and tax administration services. This research is a descriptive verification research with a survey method. This research was conducted in Majalengka with a sample of 141 individual taxpayers. Data in this study were collected using a questionnaire distributed to respondents. The results showed that the modernization of the tax administration system had an effect on individual taxpayer compliance at KPP Micro Piloting Majalengka. Modernization of the tax administration system can facilitate the work process, including facilitating the process of reporting and paying taxes. In addition, the tax authorities also have a significant effect on individual taxpayer compliance at KPP Micro Piloting Majalengka. Fiscal services also make it easier for taxpayers to carry out their tax obligations. The conclusion of this study is that the modernization of the tax administration system and tax administration services can improve individual taxpayer compliance.